2012
DOI: 10.1111/j.1752-4571.2012.00261.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutualism effectiveness and vertical transmission of symbiotic fungal endophytes in response to host genetic background

Abstract: Certain species of the Pooideae subfamily develop stress tolerance and herbivory resistance through symbiosis with vertically transmitted, asexual fungi. This symbiosis is specific, and genetic factors modulate the compatibility between partners. Although gene flow is clearly a fitness trait in allogamous grasses, because it injects hybrid vigor and raw material for evolution, it could reduce compatibility and thus mutualism effectiveness. To explore the importance of host genetic background in modulating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 49 publications
(101 reference statements)
5
66
0
Order By: Relevance
“…In addition, our results contrast with inoculation experiments that observed reduced or abnormal growth of symbionts in novel hosts (Christensen 1995, Saikkonen et al ). On the other hand, our results are consistent with a previous study that found no change in endophyte transmission following experimental crosses between host populations (Gundel et al ). Collectively, the available literature and our new results suggest that experimental inoculation studies that force novel host–symbiont associations may over‐estimate the potential for genetic incompatibility relative to approaches that measure symbiont responses to ecologically realistic outcrossing events, particularly within the grass–endophyte system.…”
Section: Discussionsupporting
confidence: 94%
“…In addition, our results contrast with inoculation experiments that observed reduced or abnormal growth of symbionts in novel hosts (Christensen 1995, Saikkonen et al ). On the other hand, our results are consistent with a previous study that found no change in endophyte transmission following experimental crosses between host populations (Gundel et al ). Collectively, the available literature and our new results suggest that experimental inoculation studies that force novel host–symbiont associations may over‐estimate the potential for genetic incompatibility relative to approaches that measure symbiont responses to ecologically realistic outcrossing events, particularly within the grass–endophyte system.…”
Section: Discussionsupporting
confidence: 94%
“…Grasses containing endophytes may be increasingly important in the face of climate changes because the symbiosis between plant and endophyte provides increased drought resistance and hardiness to the plant, and endophyte-grass interactions influence forage and pasture sustainability (Gundel et al, 2012). However, the monetary savings that may be gleaned by utilizing predominantly available forages may be negated by reduced milk production due to fescue toxicosis.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other mutualistic organisms, fungal endophytes also can alleviate pathogen and herbivore stress on plant hosts (Gundel et al 2012; Rodriguez et al 2009), but the mechanisms and ecological consequences are not well understood (see also Saikkonen et al 2013). …”
Section: Examples Of Plant-microbe Interactions That Alter Plant Phenmentioning
confidence: 99%